Silvopastoral system is an alternative to improve animal welfare and productive performance in meat production systems - Lemes, Amanda Prudêncio [UNESP]; Garcia, Alexandre Rossetto; Pezzopane, José Ricardo Macedo; Brandão, Felipe Zandonadi; Watanabe, Yeda Fumie; Cooke, Reinaldo Fernandes; Sponchiado, Mariana; de Paz, Claudia Cristina Paro; Camplesi, Annelise Carla [UNESP]; Binelli, Mario; Gimenes, Lindsay Unno [UNESP] (My University, 2021)
Climate change is a reality and global surface temperature is projected to rise substantially in the next 80 years. Agriculture practices will have to adapt to climate change, and also help to mitigate this effect using, among other strategies, forest conservation and management. Silvopastoral systems have been adopted in tropical climate livestock areas but their benefits on thermal comfort and reproductive performance of beef cows are not completely known. Therefore, our aims were to compare the microclimate of silvopastoral and intensive rotational unshaded grazing systems in different months and to evaluate physiological variables (Exp. 1 and 2), metabolism, and in vitro embryo production (Exp. 2) in crossbred beef females. Our hypothesis is that the silvopastoral system can improve the thermal comfort of beef heifers and cows and, consequently, also improve dry matter intake, body weight gain, and in vitro embryo production when compared to the unshaded rotational grazing system. In Exp 1, the silvopastoral system decreased body temperature and increased welfare and performance of heifers. In Exp. 2, the silvopastoral system enhanced the body weight but did not affect metabolism and the general reproductive performance, but increased the recovery rate of oocytes in primiparous cows.